2016
DOI: 10.1371/journal.pgen.1005982
|View full text |Cite|
|
Sign up to set email alerts
|

Caenorhabditis elegans PAQR-2 and IGLR-2 Protect against Glucose Toxicity by Modulating Membrane Lipid Composition

Abstract: In spite of the worldwide impact of diabetes on human health, the mechanisms behind glucose toxicity remain elusive. Here we show that C. elegans mutants lacking paqr-2, the worm homolog of the adiponectin receptors AdipoR1/2, or its newly identified functional partner iglr-2, are glucose intolerant and die in the presence of as little as 20 mM glucose. Using FRAP (Fluorescence Recovery After Photobleaching) on living worms, we found that cultivation in the presence of glucose causes a decrease in membrane flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
131
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(139 citation statements)
references
References 82 publications
7
131
1
Order By: Relevance
“…The worms were cultured on normal growing media plates (NGM plates) and the E. coli strain OP50 was used as a food source. The worms were maintained at the optimal temperature of 25 ° C (Sulston et al, 1988; Svensk et al, 2016). Wild type cells of S. cerevisiae (S228C background) were cultured and maintained in YPD media (Hill et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The worms were cultured on normal growing media plates (NGM plates) and the E. coli strain OP50 was used as a food source. The worms were maintained at the optimal temperature of 25 ° C (Sulston et al, 1988; Svensk et al, 2016). Wild type cells of S. cerevisiae (S228C background) were cultured and maintained in YPD media (Hill et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…We quantify it by measuring the diffusion coefficient of membrane lipids, which is inversely proportional to membrane viscosity. The acyl chain composition of membrane lipids is an important determinant of membrane fluidity and is tightly controlled in bacteria [5][6][7] , fungi 8,9 , worms 10,11 , flies 12 , and vertebrates 13,14 . Saturated lipid acyl chains tend to form non-fluid, tightly packed gel phases at physiological temperatures, whereas unsaturated lipid acyl chains fluidize the bilayer.…”
mentioning
confidence: 99%
“…2A). We found that the interaction between PAQR-2 and IGLR-2 in the gonad sheath cell membrane, where they are most abundantly expressed (9), was highly dynamic and that the strength of their interaction correlated with membrane rigidity across a range of conditions ( Fig. 2B-E).…”
mentioning
confidence: 85%